PERSEPSI TATA KELOLA DAN KOMPETENSI SUMBERDAYA MANUSIA PAUD IT INTAN INSANI KOTA BENGKULU - Wagini Wagini (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2020)
Research implemented in PAUD IT Intan Insani on location Perumnas Unib Bentiring Permai Village Muara Bangkahulu Subdistrict Bengkulu City aimed to help the PAUD governance to be better and optimal. Likert scale used as the analysis method in this research. The problem faced by PAUD IT Intan Insani are: 1. Bad governance of PAUD administration and institution 2. Teacher resource competence inadequate. Given solution through this Partnership Society Program such as: 1. Assistance training and education of governance administration and institution 2. Assistance training and education of teacher resource competence inadequate. The output that produced are: getting better governance administration and institution of PAUD IT Intan Insani, increasing of teacher resource competence so that to actualized the qualified PAUD IT Intan Insani.